The Application of Tarakanita Character Values in Children: A Case Study of Children Aged 4-5 Years - Karunia Trie, Helaria; Ardina, Mona; Fitriana, Septi; Wahyuni, Desvi (CV Media Inti Teknologi, 2025)
Background of study: Character is an attitude that should be instilled in children from an early age. Character education for early childhood education plays an important role in shaping children's moral and social foundations from an early age. Aims and scope of paper: This study aims to determine the strategies teachers use in applying Tarakanita character values to children aged 4 to 5 years at Sint Carolus Kindergarten. Methods: This study uses a qualitative approach involving the principal and two teachers as research participants. The data collection techniques used in this study are interviews and observation. Furthermore, the data will be analyzed using the Miles and Huberman model. Result: The results of the study show that Sint Carolus Kindergarten systematically develops Tarakanita character values through three main strategies, namely learning through the integration of Tarakanita Character Education, foreign languages, experience-based learning, and technology; habit formation through practicing good behavior such as queuing and caring for the environment; and reinforcement through consistent role modeling by teachers and parents as the foundation for character building in children. Conclusion: The implementation of Tarakanita character values at Sint Carolus Kindergarten is carried out through three strategies, namely learning, habit formation, and role modeling. The teachers' strategy in applying Tarakanita character values emphasizes experience-based learning and implements a cycle of reflection and sharing with parents as an effort to provide education that is consistent between home and school.